Treatment with beta-blockers, ACE inhibitors, and calcium-channel blockers is associated with a reduced fracture risk: a nationwide case-control study - Rejnmark, Lars; Vestergaard, Peter; Mosekilde, Leif (Journal of hypertension, 2006)
Cardiovascular diseases are associated with disturbances in calcium metabolism, including increased urinary calcium, vitamin D insufficiency, and decreased bone mineral density. Antihypertensive drugs may increase the risk of falling. However, risk of fracture in patients treated with non-diuretic cardiovascular drugs is largely unknown. We investigated associations between fracture risk and treatment with commonly used cardiovascular drugs: beta-blockers, angiotensin-converting enzyme (ACE) inhibitors, and calcium-channel blockers. A population-based pharmaco-epidemiological case-control study with fracture in year 2000 as outcome and drug use during the previous 5 years as exposure. We used nationwide computerized registers to assess individual use of drugs and related these data to individual fracture records and information on socio-economic and health-related confounders. We included 124,655 cases that sustained a fracture and 373,962 age and gender-matched controls. After adjustment for potential confounders, risk of any fracture was reduced by 9% [odds ratio (OR) 0.91; 95% confidence interval (CI), 0.88-0.93] in users of beta-blockers, by 6% (OR, 0.94; 95%CI, 0.91-0.96) in users of calcium-channel blockers, and by 7% (OR, 0.93; 95%CI, 0.90-0.96) in users of ACE inhibitors. Moreover, risk of hip fractures was reduced significantly by 7-14% in users of the three groups of drugs. No major differences were found between men and women or in subjects younger or older than 70 years of age. Sub-analyses indicated differences between groups of calcium-channel blockers, as use of non-dihydropyridine drugs was associated with a larger risk reduction than use of dihydropyridine drugs. Treatment with beta-blockers, ACE inhibitors, and calcium-channel blockers is associated with a small but significantly reduced risk of fracture.